ANALISIS KADAR KALSIUM OKSALAT PADA TEPUNG PORANG SETELAH PERLAKUAN PERENDAMAN DALAM LARUTAN ASAM (ANALISIS DENGAN METODE TITRASI PERMANGANOMETRI) - Wardani, Ratih Kusuma; Prasetyo Handrianto (2477 - 6165, 2019)
Tubers included in the family Araceae contain a lot of calcium oxalate. High calcium oxalate consumption in the body can cause health problems. One of these examples are in the kidneys. Tubers with high levels of calcium oxalate, if immersed in acidic solutions, calcium oxalate levels can be reduced. In this research, immersion of porang flour in starfruit juice, lime juice and vinegar with the aim that the content of calcium oxalate can be reduced. Calcium oxalate levels were analyzed by Permanganometric Titration Method. The results of this study indicate that acidic solutions can reduce calcium oxalate levels in porang flour. Calcium oxalate levels were analyzed by permanganometric titration method. The results of this study indicate that acid solution can reduce calcium oxalate levels in porang flour. The 7% Averrhoa bilimbi juice solution was able to reduce calcium oxalate levels by 62.68%. The 5% lime juice solution gaves better results than the Averrhoa bilimbi juice solution. The 5% lime juice solution could reduce calcium oxalate levels by 65.94%. The biggest decrease in calcium oxalate levels were shown in porang flour after soaking it with 20% vinegar acid solution, which amounted to 90.27%.